Nikon D5300 Digital Feild Guide - J. Dennis Thomas (John Wiley & Son, 2014)
The Nikon D5300 digital feild guide is feilled everything you need to know in oder to take amazing photographs using your new nikon. This comprehensive guide walks you throgh setting up your cemara, offers insight about wich setting to use, and tells you why each setting is userful in particular situations. Full - color imafes demontrate different photograph concepts, and show you exactly how to use the power features of your D5300